Tantangan Tantangan Tata Kelola Perikanan Tuna Berbasis Rumpon di Sulawesi Utara, Indonesia - Widhya N. Satrioajie; Sukma I. Riverningtyas; Julianto S. Hamonangan; Requel S. Membri (Universitas Pattimura, 2025)
Tuna fisheries in North Sulawesi play a significant role in supporting coastal economies and contributing to national fishery exports. A common practice in this fishery is the use of anchored fish aggregating devices (AFADs) to assist fishers in locating and catching migratory pelagic species such as tuna, skipjack, and mackerel. However, a social phenomenon that lacks clear legal recognition persists, namely the presence of FAD guards who monitor and manage these fishing grounds. This study aims to examine governance risks, social aspects, and stakeholder perceptions related to the involvement of FAD guards in fishing practices in North Sulawesi. The research employed a literature review of policy documents which is complemented by in-depth interviews with five stakeholder groups: (1) central government agencies, (2) local government institutions, (3) academics, (4) non-governmental organizations (NGOs) and (5) FAD guard representative. The findings reveal two major perspectives: (1) the FAD guard profession should be legalized as it provides livelihoods for marginalized coastal communities and supports investment and security of fishing devices, although it may encourage similar practices in other regions; and (2) the prohibition of FAD guards, as this occupation is considered high-risk and currently unregulated. These findings underscore the need for adaptive regulations, continuous stakeholder dialogue, and participatory monitoring mechanisms to ensure legal certainty and promote equitable fisheries governance.